Studies on the vignettes from chapter 17 of the Book of the Dead. - Tarasenko, Mykola, (Archaeopress Egyptology ;, 2016)
Among the numerous deities in the ancient Egyptian mythology, whose nature and function are still vague and obscure, are 'ms.w Bdśt' - 'Children of Weakness'. These beings are twice mentioned in the Book of the Dead chapter 17. The text fragments contain two local versions of the myth with 'ms.w Bdśt' - Hermopolitan (Urk. V: Abs. 1), and Heliopolitan (Urk. V: Abs. 22). Since the last text describes the combat between Re and the 'Children of Weakness', the same is likely to be reflected on the vignette, which depicts the battle of Re against 'ms.w Bdśt', metaphorically shown in the form of a serpent. This book is a comprehensive study of the 'Children of Weakness' myth and the scene depicting the cat, cutting off the head of the serpent under the branches of the 'išd'-tree found on the number of Book of the Dead chapter 17 vignettes.